الدلالات النفسية والاجتماعية في لغة الحوار القرآني : موسى عليه السلام أنموذجا - ديرشوي، أحمد محمد عطوف (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The researcher aims to deepen the understanding of the psychological and social meanings in the language of the Qur'anic dialogue contained in the story of Moses (peace be upon him). This dialogue is of linguistic importance and it is one of the efforts exerted to study the Qur'anic verses and its meanings. The researcher believes that this study can benefit society in developing their comprehension and management of the Qur'anic dialogue, and the psychological and social factors in this story, which are often highlighted through the sentences exchanged by the interlocutors and their emotions. The parties use a verbal style in expressing their position and emotion, as a method of denial, assertion, appeal, prohibition, questioning and others. The researcher follows the analytical descriptive approach and focuses on addressing the dialogue that takes place among the characters in the story and its characteristics, and identifying its implications. The research concludes that the psychological and social signifiers represent the unknown semantic dimension because they give words and sentences an expression that is not visible at times. The manifestations of psychological significance in the story of Moses are more than the manifestations of social significance. The analysis of psychological significance indicates that the Qur'anic expressions of one scene are given in different ways. The dialogue of Moses (peace be upon him) to maintain one format suggests the strictness of the speaker and his confidence in the psyche; in contrast to the dialogue of Pharaoh, who often depends on the method of assertion, threat and intimidation, which indicates the weakness of argument and evidence .